2001
DOI: 10.1126/science.1061075
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by a Secreted Lipocalin That is Transcriptionally Regulated by IL-3 Deprivation

Abstract: Many hematopoietic cells undergo apoptosis when deprived of specific cytokines, and this process requires de novo RNA/protein synthesis. Using DNA microarrays to analyze interleukin-3 (IL-3)-dependent murine FL5.12 pro-B cells, we found that the gene undergoing maximal transcriptional induction after cytokine withdrawal is 24p3, which encodes a secreted lipocalin. Conditioned medium from IL-3-deprived FL5.12 cells contained 24p3 and induced apoptosis in naive FL5.12 cells even when IL-3 was present. 24p3 also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
385
4
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(427 citation statements)
references
References 32 publications
36
385
4
2
Order By: Relevance
“…This hypothesis was furthered strengthened by the observation that NGAL induced the apoptosis of neutrophils through an autocrine pathway (Devireddy et al, 2001). In a recent publication, Tong et al (2005) showed that although NGAL expression is closely associated with apoptosis, it also favours cell survival.…”
Section: Discussionmentioning
confidence: 98%
“…This hypothesis was furthered strengthened by the observation that NGAL induced the apoptosis of neutrophils through an autocrine pathway (Devireddy et al, 2001). In a recent publication, Tong et al (2005) showed that although NGAL expression is closely associated with apoptosis, it also favours cell survival.…”
Section: Discussionmentioning
confidence: 98%
“…LCN2 encodes lipocalin 2 that can transport metal ions and fat acid (Chu et al, 1998), induce apoptosis (Devireddy et al, 2001), inhibit bacteria growth (Goetz et al, 2002), and regulate inflammatory responses (Cowland and Borregaard, 1997). It has been also reported to participate in the progression of many malignancies such as mammary tumor (Stoesz et al, 1998;Soiland et al, 2009;Yang et al, 2009), digestive tumors (Kubben et al, 2007;Zhang et al, 2007Zhang et al, , 2009), but except lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lipocalin was reported to be transcriptionally regulated by IL-3 deprivation and to induce apoptosis in IL-3-dependent pro-B cells through an autocrine pathway [28]. Although we examined the transcriptional expression of lipocalin during mast cell apoptosis induced by depletion of IL-3, we could not detect it (data not shown), suggesting a cell type-specific regulation of apoptosis.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, lipocalin, a new apoptosis-inducing molecule, which is transcriptionally regulated by deprivation of IL-3, has been reported [28]. Although the precise mechanisms are unknown, apoptosis induced by lipocalin is also inhibited by overexpression of Bcl-xL, suggesting a critical role for Bcl-xL in the anti-apoptotic effects in IL-3 deprivation-induced apoptosis [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation